2008
DOI: 10.1016/j.neuroscience.2007.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide suppresses activation of the tuberomammillary histaminergic system concomitant with behavior: A novel target of immune-sensory pathways

Abstract: Infection and inflammation strongly inhibit a variety of behaviors, including exploration, social interaction, and food intake. The mechanisms that underlie sickness behavior remain elusive, but appear to involve fatigue and a state of hypo-arousal. Because histaminergic neurons in the ventral tuberomammillary nucleus of the hypothalamus (VTM) play a crucial role in the mediation of alertness and behavioral arousal, we investigated whether the histaminergic system represents a target for immune activation and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…A recent study (40) has shown that overexpression of ⌬FosB in the ventral hypothalamus of wild-type mice is sufficient to significantly increase energy expenditure, and this supports our finding of increased ⌬FosB immunoreactivity being restricted only to hypothalamic nuclei and within the VTM of LL rats. It has been established that catecholaminergic projections ascend directly from the NTS and indirectly from the dorsal vagal complex through the ventral medulla to the VTM (14). Activity of these neurons has been studied in the context of fatigue and hypoarousal behaviors associated with sickness, but it would be interesting to investigate the importance of leptin-mediated activation of these ascending pathways and their contribution to the control of energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (40) has shown that overexpression of ⌬FosB in the ventral hypothalamus of wild-type mice is sufficient to significantly increase energy expenditure, and this supports our finding of increased ⌬FosB immunoreactivity being restricted only to hypothalamic nuclei and within the VTM of LL rats. It has been established that catecholaminergic projections ascend directly from the NTS and indirectly from the dorsal vagal complex through the ventral medulla to the VTM (14). Activity of these neurons has been studied in the context of fatigue and hypoarousal behaviors associated with sickness, but it would be interesting to investigate the importance of leptin-mediated activation of these ascending pathways and their contribution to the control of energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…These brain regions are implicated in the regulation/modulation of many facets of sickness behavior. For example, within the context of sickness the hypothalamus is critical for the regulation of body temperature, locomotor activity, feeding, drinking, and energy metabolism (Klir et al, 1993; Myers et al, 1993; Gayle et al, 1999; Elmquist et al, 2000; Gaykema et al, 2008; Szymusiak and McGinty, 2008; Thaler et al, 2012), as well as the timing of when these physiological and behavioral processes occur (Beynon and Coogan, 2010). The hippocampus is involved in aspects of cognition, learning and memory (Chen et al, 2008) that may be relevant to altered social exploration, and the brainstem is critical for aspects of autonomic responses to this insult (Kafa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fibers between the posterior hypothalamus and the mesencephalon include afferent fibers of the vagal nerve. Afferents of the vagal nerve transmit information about peripheral inflammation to the CNS, resulting in suppressed histaminergic activity and in the initiation of symptoms of sickness behavior including fatigue (Gaykema et al, 2008). Marvel et al (2004) have shown that mice with interrupted afferents of the vagal nerve do not experience sickness behavior, such as fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant correlation between T1 relaxation time in the hypothalamus and the Fatigue Severity Scale (FSS) score, indicating an association between pathological changes in the hypothalamus and MS-related fatigue. Finally, inflammation-induced suppression of histaminergic neurons was found to be associated with impaired arousal (Gaykema et al, 2008).…”
Section: Introductionmentioning
confidence: 94%